Trophic networks associated with the aphid, Rhopalosiphum maidis (Fitch) (Hemiptera: Aphididae) in a cornfield, Manabí, Ecuador - Centeno-Parrales, Jesús A. (2022)
The corn leaf aphid is considered an important pest associated with maize. This study aimed to discover the trophic associations around Rhopalosiphum maidis in Manabí, Ecuador. Maize leaves were sampled to determine the numbers of parasitized aphids, and the identities of predators and parasitoids. Nine taxa of natural enemies were detected: the primary parasitoid was Lysiphlebus testaceipes Cresson, 1880 (Hymenoptera: Braconidae); the hyperparasitoid Syrphophagus aphidivorus (Mayr, 1876) (Hymenoptera: Encyrtidae); the predatory hoverfly Ocyptamus dimidiatus (Fabricius, 1781) (Diptera: Syrphidae), four species of coccinellids, Cheilomenes sexmaculata (Fabricius, 1781), Cycloneda sanguinea (Linnaeus, 1763), Hippodamia convergens Guerin-Meneville, 1842 and Paraneda pallidula guticollis (Coleoptera: Coccinellidae) and an assassin bug, Zelus sp. (Hemiptera: Reduviidae). A parasitoid, Pachyneuron formosum Walker, 1833 (Hymenoptera: Pteromalidae) emerged from hoverfly pupae. This study reports the presence of the parasitoids S. aphidivorus and P. formosum in Ecuador for the first time. These results increase the knowledge of a four-trophic level relationship (host plant – pest – parasitoids, predators – hyperparasitoids) in a maize agroecosystem as a fundamental basis for biological control programs.